AGAR MATA AIR TIDAK MENJADI ‘AIR MATA’ Dinamika Pengelolaan Sumber Daya Air di Era Otonomi Daerah Studi Kasus di Desa Tajuk, Kec. Getasan, Kab. Semarang - Istiyani, Ambar (Universitas Kristen Satya Wacana, 2016)
This paper describes a research finding on the dynamics of water management in decentralization era using a case study in Tajuk Village, Semarang Regency. The case study shows the change of water management system in the village. Water-based conflict was often happened due to inequity of water distribution to the community. Water management changes when Pamsimas (Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat) program enters the village, a program established by central government in cooperation with local government as an implementation of decentralization. In the beginning, the program invites pro and con among villagers. The pro side argues that the program can solve community’s problem on the inequity of water distribution, while the conside argues that the public should not pay to water which is their own asset. Finally, the program was implemented when all community members were convinced that they themselves who will manage and decide the price of water in the village.Kata kunci: pengelolaan sumber daya air, konflik, desentralisasi, Pamsimas